1987
DOI: 10.1021/j100293a017
|View full text |Cite
|
Sign up to set email alerts
|

Arylaminyl radicals studied by laser flash photolysis of di-tert-butyl peroxide in the presence of arylamines

Abstract: Arylaminyl Radicals Studied by Laser Flash Presence of Arylamines that case.5,8,9 Because N2(A) metastables serve to carry these chains, species capable of quenching these metastables (e.g., NO) may well act to stabilize gaseous samples of the halogen azides.Acknowledgment. We are grateful to Professor J. Anderson of Harvard University for kindly loaning to us the computer program used for the calculations described above. This work was supported by the U.S. Air Force Weapons Laboratory under Contract No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 2 publications
9
35
1
Order By: Relevance
“…As shown in the bottom half of figure 1, a hydrogen atom transfer mechanism can also explain aromatization of the dihydropyridine and radical formation. In this mechanism mechanism, hydrogen atom abstraction from nitrogen (Leyva et al 1987) the formation of an aminyl radical, which can aromatize by loss of the Cq alkyl group as a free radical. This mechanism has the attractive feature that it rationalizes the observation that two N-alkyl dihydropyridine Hantzsch esters do not inactivate P450 until their alkyl groups are first oxidatively removed (Lee et al 1988).…”
Section: Je-mentioning
confidence: 99%
“…As shown in the bottom half of figure 1, a hydrogen atom transfer mechanism can also explain aromatization of the dihydropyridine and radical formation. In this mechanism mechanism, hydrogen atom abstraction from nitrogen (Leyva et al 1987) the formation of an aminyl radical, which can aromatize by loss of the Cq alkyl group as a free radical. This mechanism has the attractive feature that it rationalizes the observation that two N-alkyl dihydropyridine Hantzsch esters do not inactivate P450 until their alkyl groups are first oxidatively removed (Lee et al 1988).…”
Section: Je-mentioning
confidence: 99%
“…An absorption band, which matches the literature value for the diphenylamine radical cation, appears immediately after the laser pulse at 680 nm (18). The signal at 680 nm decays within 2 μs, and a new signal corresponding to the literature value for the neutral diphenylamine radical appears at 710 nm (19). A new signal is also seen at 450 nm 1.5 μs after the laser pulse.…”
Section: Resultsmentioning
confidence: 55%
“…The importance of alkoxyl radicals in organic, biological, and atmospheric chemistry has motivated numerous studies on their reactions. Most of these studies have been carried out employing tert-butoxyl radicals and have shown that these radicals rapidly abstract hydrogen from different substrates, such as hydrocarbons [l-51, ethers [6], alcohols [2,7], sulfides [8], and alkylamines [9-111 to give carbon-centered radicals and from phenols [12], silanes [13], and aryl amines [14] to give the corresponding heteroatom centered radicals. In general, the rate of the process has been interpreted in terms of the strength of the broken bond and the contribution of charge transfer configurations to the critical energies.…”
Section: Introductionmentioning
confidence: 99%
“…Among the families of compounds bearing reactive hydrogen atoms and aromatic conjugated double bonds stand the indole derivatives. For indole, it has been reported that tert-butoxyl radicals abstract the hydrogen atom from the nitrogen giving the indolyl radical [14]. However, other radicals react in a different and more complex way.…”
Section: Introductionmentioning
confidence: 99%